2019
DOI: 10.1097/sla.0000000000003661
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of the Treatment of Appendicitis in America

Abstract: Objective: We sought to describe contemporary presentation, treatment, and outcomes of patients presenting with acute (A), perforated (P), and gangrenous (G) appendicitis in the United States. Summary Background Data: Recent European trials have reported that medical (antibiotics only) treatment of acute appendicitis is an acceptable alternative to surgical appendectomy. However, the type of operation (open appendectomy) and average duration of stay are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 25 publications
5
44
0
Order By: Relevance
“…CT seems to be commonly used both in adults (83%) and in children (73%) with AA in hospitals in the United States [ 17 ], despite the increased risk of hematologic malignancies in young adults related to ionizing radiation [ 18 ]. Recent studies by Yeh et al and by Sugiura K et al included patients with already diagnosed acute appendicitis, where their reported NA rate was 10% and 2.5% with 85% and 95% use of preoperative CT. Their experience of US use was very limited—14% and 19%, respectively [ 19 , 20 ]. Our results, which highlight the importance of the conditional CT strategy, are similar to a previous study [ 21 ] where the TUS was able to identify the appendix in 53% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…CT seems to be commonly used both in adults (83%) and in children (73%) with AA in hospitals in the United States [ 17 ], despite the increased risk of hematologic malignancies in young adults related to ionizing radiation [ 18 ]. Recent studies by Yeh et al and by Sugiura K et al included patients with already diagnosed acute appendicitis, where their reported NA rate was 10% and 2.5% with 85% and 95% use of preoperative CT. Their experience of US use was very limited—14% and 19%, respectively [ 19 , 20 ]. Our results, which highlight the importance of the conditional CT strategy, are similar to a previous study [ 21 ] where the TUS was able to identify the appendix in 53% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Conservatively, patients were initially treated with intravenous-antibiotic inpatient treatment for 3 days, with continued uncertainty about the further course of the disease. Thereafter, 27–46% of the patients underwent surgery during the following 1–5 years because of an at least suspected disease recurrence [8, 13, 14, 18, 26]. Leaving the conservatively treated patients in uncertainty whether the disease might strike again obviously results in some kind of appendicitis anxiety described in the literature [27].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The open surgical technique that was compared to conservative treatment within the publication of Salminen et al [4], which is now more than 5 years ago, is no longer state of the art at least in Germany [21]. This is highlighted above all in an American collective study which, with also a 98% rate of minimally invasive interventions and a routine hospital stay of around 24 h postoperatively, is openly questioning the conservative treatment approach in Europe [26].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations